STRATEGI BISNIS UNTUK MEMPERTAHANKAN PENJUALAN JASA PENGIRIMAN KARGO FREIGHT FORWARDING PADA MASA PANDEMI COVID-19 - Agus Prasetyo; Adijati Utamingsih; Paulus Wardoyo (Magister Manajemen STIE Bank BPD Jateng, 2023)
The purpose of this study is to understand business strategies in maintaining sales of cargo shipping services for Freight Forwarding companies engaged in exports and imports during the covid 19 pandemic. Facing competition, every freight forwarding company must have the right business strategy in order to maintain sales of its cargo shipping services. most of which experienced a decline during the COVID-19 pandemic. The strategy is designed through a SWOT analysis by knowing the company's internal (IFE) and external (EFE) factors. The research used a descriptive qualitative approach. Data was collected through in-depth interviews with key informants from the management of the freight forwarding company, such as the President Commissioner, Director, Operations Manager, Finance and Accounting Manager, Customer Service and Sales, employees of the Eczema document department and service users. With SWOT analysis in improving cargo delivery services, the company is positioned among Strength-Opportunities by leveraging strengths to seize and take advantage of the greatest opportunities. Through the IE matrix, the company is in a position to grow and develop alternative strategies that can be implemented, namely forward integration, backward integration, horizontal integration, product development, business development, market penetration, and related diversification